Optimization of Au Bowtie Nanoantenna Array Considering Both Field Enhancement and Thermal Endurance for High-order Harmonic Generation - Kim, Yong Soo; Jeong, Yeongkon; An, Young Jun; Yu, Byung Deok; Lee, Ju Han; Jhon, Young Min (Springer Verlag, 2025)
Localized surface plasmon resonance (LSPR) is a phenomenon that confines and enhances electromagnetic fields at the nanoscale and has been studied theoretically and experimentally in various nanostructured antennas. Among them, the bowtie nanoantenna maximizes the LSPR effect by creating a nanogap at the sharp opposing vertices of two facing triangular structures. In addition, the unique geometric design of a bowtie nanoantenna enables flexible customization for a wide range of applications. In this study, a nanoantenna was designed to enhance the infrared driving laser intensity in high-order harmonic generation (HHG). This study aimed to maximize the E-field enhancement with an LSPR resonance wavelength around 800 nm range while improving the thermal endurance of the antenna using a diamond substrate with exceptionally high thermal conductivity. Finite element method simulations for electromagnetic wave (EMW) and heat transfer were conducted using COMSOL Multiphysics, leading to the determination of optimal geometric parameters. The LSPR resonance wavelength was 840 nm with an E-field enhancement of 710 when the antenna width was 100 nm, height 200 nm, nanogap 10 nm, period 250 nm, and thickness 30 nm. Furthermore, the peak temperature at the nanogap of the bowtie antenna was 3297 K, which is 2349 K lower than the value reported in our previous study. The proposed optimized parameters suggest that the nanoantenna can withstand higher laser intensities without structural failure, enabling the generation of high-power, ultrahigh-order harmonics.